Performance monitoring and behavioral adaptation during task switching: An fMRI study. (29th January 2015) - von der Gablentz, J.; Tempelmann, C.; Münte, T.F.; Heldmann, M.
Highlights: Task switching recruits the locus coeruleus. Hippocampus and parahippocampal gyrus are engaged by learnable stimulus–response associations. Performance monitoring and response adaptation involve partially overlapping brain networks. Abstract: Despite significant advances, the neural correlates and neurochemical mechanisms involved in performance monitoring and behavioral adaptation are still a matter for debate. Here, we used a modified Eriksen–Flanker task in a magnetic resonance imaging (MRI) study that required the participants to derive the correct stimulus–response association based on a feedback given after each flanker stimulus. Participants had to continuously monitor and adapt their performance as the stimulus–response association switched after a jittered time interval without notice. After every switch an increase of reaction times was observed. At the neural level, the feedback indicating the need to switch was associated with activation of the precuneus, the cingulate cortex, the insula and a brainstem region tentatively identified as the locus coeruleus. This brainstem system appears to interact with this cortical network and seems to be essential for performance monitoring and behavioral adaptation. In contrast, the cerebellum crus and prefrontal areas are activated during error feedback processing. Furthermore we found activations of the hippocampus and parahippocampal gyrus bilaterally after a correct feedback in learnable stimulus–response associations. These results highlight the contribution of brainstem nuclei to performance adaptation.